2021
DOI: 10.1038/s41598-021-90280-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel source of salt tolerance in local bread wheat germplasm using morpho-physiological and biochemical attributes

Abstract: Salt tolerant wheat cultivars may be used as genetic resource for wheat breeding to ensure yield stability in future. The study was aimed to select salt tolerant cultivar(s) to identify novel source of salt tolerance in local wheat germplasm. Initially, 40 local wheat cultivars were screened at 150 mM NaCl stress at seedling stage. Selected salt-tolerant (three; S-24, LU-26S and Pasban-90) and salt-sensitive (four; MH-97, Kohistan-97, Inqilab-91 and Iqbal-2000) wheat cultivars were further evaluated using grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Positive correlations between parameters of tolerance to salinity measured in the early growth stages and those measured at full maturity were reported by El-Hendawy et al [19] and Turki et al [69]. Furthermore, Dugasa et al [70] and Hussain et al [71] reported that a reduction in wheat grain yield (phenophase of full maturity) was associated with a decrease in morphological parameters measured in the tillering phenophase.…”
Section: Discussionmentioning
confidence: 63%
“…Positive correlations between parameters of tolerance to salinity measured in the early growth stages and those measured at full maturity were reported by El-Hendawy et al [19] and Turki et al [69]. Furthermore, Dugasa et al [70] and Hussain et al [71] reported that a reduction in wheat grain yield (phenophase of full maturity) was associated with a decrease in morphological parameters measured in the tillering phenophase.…”
Section: Discussionmentioning
confidence: 63%
“…The selected tolerant and sensitive genotypes were re-evaluated in a further study to identify the biochemical, physiological, and ionic mechanisms of salinity tolerance. The better performance of salt-tolerant genotypes under stress conditions was found to be associated with maintenance of high K + /Na + ratio, photosynthetic activity, accumulation of osmotic regulators, and higher activities of antioxidant enzymes that minimize the production of ROS [ 39 , 40 , 41 ]. The results of these studies were found consistent with our experimental findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, a significant reduction in biomass of Fareed-06 and Kohistan-97 was observed. Under saline conditions, less reduction in biomass or crop yield will determine the salt tolerance variety ( Hussain et al, 2021 ). The yield of a wheat crop depends upon many yield-related traits such as grain, numbers, and the size of grains.…”
Section: Discussionmentioning
confidence: 99%